CoFe2O4 nanopowder synthesis by a solid-liquid cation-exchange process and their magnetic properties. Issue 10 (15th May 2021) - Liu, Lingyu; Wang, Zihua; Wang, Xue Zhong
Abstract: A sol-gel method using highly compacted sodium alginate (Na-ALG) granules as gelation media was developed for the synthesis of CoFe2 O4 (CFO) nanoparticles in this study. The high shear wet granulation (HSWG) process was applied with the granule size distribution (GSD), as measured and simulated using the population balance model (PBM). The formation of CFO nanoparticles was confirmed by powder X-ray diffraction (XRD). The mean crystallite sizes calculated using XRD Rietveld refinement analysis matched the particle sizes observed by transmission electron microscopy (TEM). The magnetic properties of the obtained CFO nanoparticles under different heat treatment conditions were measured using a vibrating sample magnetometer (VSM) at room temperature. As the calcination temperature increased, larger particles with higher crystallinities were obtained, which resulted in the overall magnetic properties increasing logarithmically as a function of crystalline size. The maximum saturation magnetization (76.61 emu/g) was obtained using the sample calcined at 900 °C for 2 h.